Aberrant SNHG expression predicts poor prognosis in esophageal cancer using meta-analysis and bioinformatics analysis - Ke Shi; Li-De Huang; Dan Li; Wei-Min Luo; Hua-Song Liu; Dong-Xiao Ding; Qiang Guo; Yue-Feng Liu (BMC Gastroenterology)
Abstract Background Small nucleolar RNA host gene (SNHG) family were reported involved in various biological processes and may be used as a promising prognostic marker in esophageal cancer (EC). A meta-analysis was performed to investigate the relationship between SNHG expression and prognosis of EC in this study. Methods Relevant databases were browsed to obtain suitable publications. Hazard ratio (HR) with 95% confidence interval (CI) were extracted to explore the association between SNHG expression and EC prognosis. Odds ratio (OR) with 95%CI were extracted to assess the association between SNHG expression and other clinicopathological parameters. Sensitivity analysis and publication bias were performed to explore the reliability and robustness of the results. Bio-informatics has been explored in order to confirm our conclusions more comprehensively. Results 16 studies comprising 1229 patients were enrolled. The results showed that increasing SNHG expression indicated worse overall survival (HR: 1.392, 95%CI = 0.876–1.908). SNHG2, SNHG5, and SNHG12 were down-regulated, while other SNHGs were up-regulated in EC. In populations with low expression of SNHG2, SNHG5, and SNHG12, increasing SNHG expression predicted a favorable cancer prognosis (HR: 0.511, 95%CI = 0.322-0.700). Conversely, in populations with high expression of other SNHGs, SNHG expression indicated poor prognosis (OR: 2.340, 95%CI = 1.744–2.936). Elevated SNHG expression also implied advanced TNM stage (OR 1.578, 95%CI = 1.273–1.956) and lymph node metastasis (OR: 1.533, 95%CI = 1.205–1.950). Conclusion Increased expression of SNHG2, SNHG5, and SNHG12, and decreased expression of other SNHGs tended to have a favorable prognosis in patients with EC. These findings suggest that SNHG may serve as a prognostic marker and therapeutic target for EC.